An Analysis of Issues for Adoption of Cloud Computing in Telecom Industries - Ramzan, M.; Farooq, M. S.; Zamir, A.; Akhtar, W.; Ilyas, M.; Khan, H. U. (Engineering, Technology & Applied Science Research, 2018)
In the modern era companies seek the use of modern technologies in order to upgrade their infrastructure and enhance their business growth. The use of business intelligence, data science and cloud computing (CC) has become an integral part of business. Different factors play important role in the adoption of cloud services. An organization willing to adopt cloud services should consider them. This paper explores the factors and addresses the issues in implementing and deploying CC in telecom companies. In addition, this study also shares the benefits of utilizing CC which is a novel technical pattern which can change the use of different associations of information technology as a service. CC concentrates on the idea of definition, security problems, service models and infrastructures of its development. The important point is to analyze how this paradigm should be adopted in telecom industries and its results. This research study presents a comparative analysis of adaptation of CC by various telecom industries. The results identify certain limitations which also play their role for adaptation of CC in telecom companies.